Tears for water : songbook of poems and lyrics - Keys, Alicia (Berkley Books, 2005)
Presents a collection of poems and lyrics by Grammy Award winner, singer-songwriter, and musician Alicia Keys depicting the joy, pain, sorrow, and depression of her life.